Differential amplification and contraction of satellite DNAs in the distinct lineages of the beetle Euchroma gigantea - Félix, Aline Priscila; Amorim, Igor Costa de; Milani, Diogo [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Moura, Rita Cássia (Elsevier, 2024)
Satellite DNA (satDNA) consists of tandem repeat sequences that typically evolve rapidly through evolutionary mechanisms, including unequal crossover, transposition events, and others. The evolutionary history of Euchroma gigantea is marked by complex chromosomal evolution between lineages, making this species an interesting model for understanding satDNA evolution at intraspecies level. Therefore, our aim was to comprehend the potential contribution of satDNAs to the greater chromosomal differentiation of evolutionary lineages in E. gigantea by investigating the differential patterns of amplification and contraction of the repeats. To achieve this, we employed de novo identification of satDNA using RepeatExplorer and TAREAN, allowing the satellitome characterization between lineages. A total of 26 satDNA families were identified, ranging from 18 to 1101 nucleotides in length, with most families being shared between individuals/lineages, as predicted by the library hypothesis, except for the satDNA EgiSat21-168 that was absent for Northeast Lineage. The total satDNA content of the individuals was less than 11.2%, and it appeared to increase in two directions following the chromosomal evolution model. Thirteen satDNAs exhibited different patterns of amplification, and nine ones were contracted among individuals. Additionally, most repeats showed a divergence of about 10% for these satDNAs, indicating satellitome differentiation for each lineage/individual. This scenario suggests that the expansion of the satellitome occurred differentially among individuals/lineages of E. gigantea, with the contribution of various DNA turnover mechanisms after geographical isolation, and that they could be involved with karyotype evolution.
Keywords: Differential amplification; Insects; Satellite DNA; Satellitome analysis